Model pengalaman pengguna interaksi gerak isyarat dalam warisan maya - Normala Rahim
User eXperience (UX) is important for attracting users to stay and keen to interact with virtual heritage. Literature studies and interviews with 10 users show that the UX effect is less effective after users explore the virtual heritage environment as the user interface design is still based on conventional paradigms and information delivery methods on related artefacts failed to visual effectively. This research is to develop a gesture interaction model in the museum environment as a virtual heritage based on actual user experience. User-Centred Design method is used which focus on information experts and enjoyer as users. The result of the user requirement analysis for interaction of gesture via the triangulation method (contextual inquiry; six experts, questionnaires; 32 actual users and guessability studies; 13 actual users) have proven that the technology in virtual reality platforms within hand gesture technique and information display through digital storytelling technique is required to stimulate knowledge and increase UX levels. All 100% of respondents need a clear information about each artefact and 78% of respondents require to touch the artefacts displayed in the gallery. Additionally, each of the displayed artefacts should consider aspects of knowledge dissemination to visitors (85%). Whereas the heuristic evaluation of five experts in the design phase has shown the Content Validity Index (CVJ) is calculated and the result is 0.98 proving that the design of the prototype interface is designed according to the specification of the targeted user's requirements. Then, the model (Gesture based interaction by combining digital STorytelling for virtual heritage based on user eXperience - GeSToUX) was developed including construct of instrumental, non-instrumental, emotional effects, usability and loyalty through a prototype (Gua Bewah Virtual Heritage - GBYH). The validation of the GeSToUX model through questionnaire technique showed that the mean score of the overall user experience level of the prototype was high (mean = 6.35 out of 7.00). Thus, GeSToUX can serve as a guide for designers and developers of virtual legacy systems.